2021
DOI: 10.3389/fped.2021.684418
|View full text |Cite
|
Sign up to set email alerts
|

Extracurricular Physical Activities and the Condition of Being an Only Child as a Conditioning Factor in the Psychomotor Development of 5-Year-Old Children

Abstract: In early childhood education, there is a great interdependence among motor, affective, and cognitive development. A better understanding of psychomotor development and its variables by pediatricians and those who oversee educational tasks at this stage of development, such as teachers, psychologists, counselors, and parents themselves, can influence the design of educational intervention proposals. To that effect, the present study aims to analyze the influence of some family characteristics such as the condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Although the literature indicates, in general terms, that the practice of extracurricular physical activities favors FMS ( Kokštejn et al, 2017 ), when the results obtained in different studies are analyzed in detail, it is found that not all FMS are benefited by this type of activity. Thus, for example, there are studies that show that in children as young as those that make up this sample, and also Spanish, only some motor components were benefited by these extracurricular activities ( Gil-Madrona et al, 2021 ; Honrubia-Montesinos et al, 2021 ). Further research is required to clarify what characteristics should have motor extracurricular experiences to enhance the different FMS.…”
Section: Discussionmentioning
confidence: 96%
“…Although the literature indicates, in general terms, that the practice of extracurricular physical activities favors FMS ( Kokštejn et al, 2017 ), when the results obtained in different studies are analyzed in detail, it is found that not all FMS are benefited by this type of activity. Thus, for example, there are studies that show that in children as young as those that make up this sample, and also Spanish, only some motor components were benefited by these extracurricular activities ( Gil-Madrona et al, 2021 ; Honrubia-Montesinos et al, 2021 ). Further research is required to clarify what characteristics should have motor extracurricular experiences to enhance the different FMS.…”
Section: Discussionmentioning
confidence: 96%
“…The social context in which the child is embedded might also shape the saliency patterns of the child, that is, the sensory data and experiences that the child will tend to pay attention to. Having a sibling, for instance, is speculated to stimulate more imitation-based learning whereas being an only child is thought to evoke more learning through independent exploration (Gil-Madrona et al, 2021). In extension, only children might be more likely to reap benefits of having access to natural features and environments than children with one or more siblings.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that the birth order position of a child is related to the amount of behavioral problems and that in turn, the amount of behavioral problems is related to the motor performance of a child. A previous study investigated the relationship between the presence of siblings on the one hand and motor skills and socio-emotional skills on the other hand [ 41 ]. This study reported that the presence of siblings was not related to motor skills, while children with siblings scored higher on social relations (i.e., being able to establish relationships, sharing with others, showing respect toward others, and showing both positive and negative emotions while playing with others) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study investigated the relationship between the presence of siblings on the one hand and motor skills and socio-emotional skills on the other hand [ 41 ]. This study reported that the presence of siblings was not related to motor skills, while children with siblings scored higher on social relations (i.e., being able to establish relationships, sharing with others, showing respect toward others, and showing both positive and negative emotions while playing with others) [ 41 ]. In other words, having siblings to play with during childhood might train a child in establishing social relationships with others and how to behave during these interactions.…”
Section: Discussionmentioning
confidence: 99%